Republic of Latvia : Fourth Review Under the Stand-By Arrangement and Financing Assurances Review, Request for Rephasing of Purchases Under the Arrangement and Request for Waiver of Nonobservance of a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2011)
Strong policy implementation under the Stand By-Arrangement (SBA) has contributed to Latvia's economic recovery and put attainment of Maastricht criteria for euro adoption within reach. The government has continued to achieve substantial fiscal savings and strengthened its active labor market policy. Executive Directors stressed the need to implement plans for reforming state-owned banks and to promote market-based debt restructuring. Directors advised to maintain strong budget implementation in 2011 and focus on reducing taxes in the 2012 budget. They encouraged to enhance efficiency of state-owned enterprises to keep inflation under control.